On the Variation of Turbulence in a High-Velocity Tidal Channel - Charles Greenwood; Arne Vogler; Vengatesan Venugopal (Energies, 2019)
This study presents the variation in turbulence parameters derived from site measurements at a tidal energy test site. Measurements were made towards the southern end of the European Marine Energy Centre’s tidal energy test site at the Fall of Warness (Orkney, Scotland). Four bottom mounted divergent-beam Acoustic Doppler Current Profilers (ADCPs) were deployed at three locations over an area of 2 km by 1.4 km to assess the spatial and temporal variation in turbulence in the southern entrance to the channel. During the measurement campaign, average flood velocities of 2 ms−1 were recorded with maximum flow speeds of 3 ms−1 in the absence of significant wave activity. The velocity fluctuations and turbulence parameters show the presence of large turbulent structures at each location. The easternmost profiler located in the wake of a nearby headland during ebb tide, recorded flow shielding effects that reduced velocities to almost zero and produced large turbulence intensities. The depth-dependent analysis of turbulence parameters reveals large velocity variations with complex profiles that do not follow the standard smooth shear profile. Furthermore, turbulence parameters based on data collected from ADCPs deployed in a multi-carrier frame at the same location and time period, show significant differences. This shows a large sensitivity to the make and model of ADCPs with regards to turbulence. Turbulence integral length scales were calculated, and show eddies exceeding 30 m in size. Direct comparison of the length scales derived from the streamwise velocity component and along-beam velocities show very similar magnitudes and distributions with tidal phase.